Skrining Oportunistik untuk Mendeteksi Diabetes Melitus yang Baru Terdiagnosis - Sri R Paputungan; Fabiola MS Adam; John MF Adam (Jurnal Kardiologi Indonesia, 2013)
Background. It is estimated that 50% of the diabetic patients are undiagnosed.Opportunistic screening is one of the screening method, to detectnewly diagnosed diabetes mellitus. The aim of this study is to detect theundiagnosed diabetes mellitus by screening in the clinical setting.Subjects and Methods. Subjects were form the EIDEG screening fordiabetes mellitus. The procedure is a two step screening, first using thereflectance meter for capillary blood sugar, followed by confirmation testin the laboratory. Capillary blood sugar was divided into 3 groups, < 100mg/dL as normal, 100-199 mg/dl possible diabetes, and ? 200 mg/dL suspecteddiabetes. For group two, an OGTT was performed, and for groupthree, only FPG. Diabetes mellitus was diagnosed if FPG ? 126 mg/dl andor 2 hour OGTT ?200 mg/dl.Results. During the screening, 4737 subjects can be screened, only 1654completed the screening. Diabetes mellitus was diagnosed in 240 subjectsor 14.5%. There were more females compared to males, 52,9% and 47,1%subsequently, most were at the age ?50 years. More diabetic patients werediagnosed by OGTT compared to FPG only.Conclusions. This study showed that opportunistic screening may detectmore diabetic patients. It is suggested that this screening procedure canbe used by every clinicians in their daily practice.